Single dose HPV (Human Papilloma Virus) Vaccination for Cervical Cancer Prevention in Pakistan - Sadiah Ahsan (Journal of the Pakistan Medical Association, 2025)
Pakistan is launching the HPV Vaccine in September 2025,in its EPI (Expanded Programme for Immunization) for 9 to14 year old girls. This has been suggested by Professionalorganizations in Pakistan including SOGP (Society ofObstetricians & Gynaecologists) and AMAN (Associationfor Mothers & Newborns.1 At the 2nd Global CervicalCancer Elimination Forum held recently, world leadersannounced new investments and policy pledges toexpand access to HPV vaccination, screening andtreatment – bringing the world closer to making cervicalcancer the first cancer ever to be eliminated.2 HPVvaccination can prevent the majority of cases. Combinedwith screening and timely treatment for precancerousCervical intraepithelial neoplasia (CIN) and invasivecancer, it can lead to elimination. However, in 2024 only 46% of low-income countries introduced HPV vaccinationnationally, compared to 98% of high-income nations. Continue...